Controlled trial of a new cervical spatula. Issue 6563 (3rd January 1987) - Wolfendale, M R; Howe-Guest, R; Usherwood, M M; Draper, G J
Abstract : A wooden spatula was designed to scrape the varied distribution of epithelial abnormalities of the cervix as seen at colposcopy. The efficiency of the spatula in obtaining dyskaryotic cells and improving the cellular quality of smears was compared with that of the Ayre spatula in a controlled trial. More than 17, 000 smears were taken from women aged 14-86 years by more than 200 smear takers from 74 centres. Twenty two per cent more dyskaryotic smears were obtained with the trial spatula, and the cellular quality of the smears was improved in all age groups. Although it was associated with a slightly increased risk of bleeding, 83% of users preferred the trial spatula.